Influência da adição de Nb e da temperatura de tempera nas propriedades mecânica, termicas, estruturais e na corrosão de uma liga CuAlNi - Dias, Elisabeth Aline de Melo Gomes Soares (2022)
Cu-Al-Ni alloys are suitable for high temperature applications due to their high thermal stability. In contrast, Cu-Al-Ni alloys produced by typical casting methods show excessive brittleness associated with the high average grain size (about several millimeters) and their elastic anisotropy. One way to overcome this fragility is through the addition of inoculants. In this sense, the present work aimed to evaluate the influence of Nb addition and tempering temperature on the mechanical, thermal, structural and corrosion properties of a CuAlNi alloy. The CuAlNi and CuAlNbNi alloys were elaborated under ambient atmosphere and characterized by microscopy, X-ray diffraction, Differential Scanning Calorimetry and corrosion. In addition, the influence of Nb and tempering temperature on Vickeres microhardness was evaluated. Our results demonstrated that the studied alloys presented the martensite and austenite phases at room temperature. The addition of Nb modified the microstructure of the CuAlNi alloy, from an equiaxed to a columnar structure, and did not significantly affect the corrosion potential. However, the alloy with Nb and solubilized at a temperature of 850 ºC showed the highest corrosion current density. It was also verified a dependence of the corrosion current density and microhardness with the solubilization temperature of the CuAlNiNb alloy.